1993
DOI: 10.1016/0014-5793(93)80091-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of muscle pyruvate oxidation during late pregnancy

Abstract: Despite significant increases in circulating concentrations of lipid fuels (triacylglycerol, non-esterified fatty acids (NEFA) and ketone bodies) in late-pregnant rats sampled in the fed (absorptive) state, cardiac and skeletal muscle active pyruvate dehydrogenase (PDH& activities remained comparable with those observed in fed, age-matched virgin controls. Cardiac PDH, activity was suppressed in response to acute (6 h) starvation in late-pregnant (as well as virgin) rats: this inactivation was opposed by inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…PDH a activities were measured in extracts of freezeclamped muscles from rats sampled in the basal state (24 h starved) and after 2 h of insulin-stimulation during refeeding ( Figure 4). In order to assess the extent of reversal of PDH inactivation by phosphorylation that is well-established to occur in response to starvation (Caterson et al, 1982;Holness et al, 1989;Sugden and Holness, 1993), PDH a activities have been expressed relative to those pertaining in the fed state in control (virgin) rats.…”
Section: Insulin-sensitive Targets Distal To Glucose Uptake: Glycogenmentioning
confidence: 99%
See 1 more Smart Citation
“…PDH a activities were measured in extracts of freezeclamped muscles from rats sampled in the basal state (24 h starved) and after 2 h of insulin-stimulation during refeeding ( Figure 4). In order to assess the extent of reversal of PDH inactivation by phosphorylation that is well-established to occur in response to starvation (Caterson et al, 1982;Holness et al, 1989;Sugden and Holness, 1993), PDH a activities have been expressed relative to those pertaining in the fed state in control (virgin) rats.…”
Section: Insulin-sensitive Targets Distal To Glucose Uptake: Glycogenmentioning
confidence: 99%
“…Significant suppression of glucose utilization by oxidative muscles of late (19-20 day) pregnant rats is also associated with hepatic and peripheral insulin resistance (Leturque etal., 1984) and high levels of plasma fatty acids (Leturque et al, 1989;Holness et al, 1991;Sugden and Holness, 1993). The state of insulin resistance induced by late pregnancy is not further enhanced by high-fat feeding (Leturque etal., 1987).Taken together, these findings suggest that an increase in fatty acid oxidation may underlie the suppression of glucose utilization observed in oxidative muscles during pregnancy.…”
Section: Introductionmentioning
confidence: 97%
“…6 Previous studies in rats showed that the heart reduces its glucose consumption, by as much as 75% by late pregnancy, and fulfilling its needs instead with fatty acids. 79 Recently, cardiac nitric oxide (NO) synthesis and endothelial NO synthase (eNOS) were shown to increase by late pregnancy, which was accompanied by a decrease in glucose uptake and use, and a corresponding increase in fatty acid uptake. 10, 11 The mechanism for this substrate switch, however, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, PDHa activities in skeletal muscle in pregnancy in the fed state (i.e. when insulin levels are high) are similar to those of non-pregnant controls[26]. There is thus every indication that even though adipose-tissue lipolysis is resistant to suppression by insulin in the fed state in pregnancy, the oxidation of available FA by muscle is restricted and incoming acyl CoA is esterified rather than oxidized.…”
mentioning
confidence: 97%
“…70 microunits/ml) is unable to normalize plasma NEFA concentrations[25]. Enhanced adipose-tissue lipolysis within 6 h of the onset of starvation in pregnancy is associated with significant suppression of skeletalmuscle PDHa activities[26], findings that strongly suggest an accelerated switch to the oxidation of lipid-derived fuels by maternal skeletal muscle at low insulin concentrations. However, PDHa activities in skeletal muscle in pregnancy in the fed state (i.e.…”
mentioning
confidence: 99%